The Overexpression of TGF-β and CCN2 in Intrauterine Adhesions Involves the NF-κB Signaling Pathway - Xue, Xiang (PLoS One, 2015)
Intrauterine adhesions (IUA) are a significant cause of menstrual disturbance and infertility, but their pathogenesis still remains unclear. Here, we investigated the expression of TGF-β and CCN2 in IUA endometrial tissue by immunohistochemistry, western blotting and qRT-PCR assays, and found the expression of TGF-β and CCN2 in the endometrial tissue of IUA was significantly increased compared to normal endometrium and uterine septum (P<0.01), suggesting that TGF-β and CCN2 may play an important role in the formation of IUA. Moreover, the activity of the NF-κB signaling pathway in endometrial tissue of IUA was also significantly enhanced compared to normal endometrial and uterine septum (P<0.01) and positively correlated with the expression of TGF-β and CCN2, which suggested that TGF-β and CCN2 expression may be involved in the NF-κB signaling pathway. Blocking the NF-κB signaling pathway using SN50 resulted in the reduced expression of TGF-β in RL95-2 cells, which confirmed the association of the NF-κB signaling pathway and TGF-β in endometrial cells. Additionally, the expression of TGF-β and CCN2 was associated with IUA recurrence, which provides a potential prognostic indictor for IUA. Together, these results demonstrated that TGF-β and CCN2 play an important role in IUA formation, whose mechanism was associated with the activation of the NF-κB signaling pathway.